Benin : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
This paper examines the external sustainability and competitiveness of Benin's economy. Balance of payments flows suggest Benin's external position is sustainable. Large trade and current account deficits are comfortably financed by inflows through the capital and financial accounts, in particular project grants and loans, private capital, and inflows to commercial banks. It is estimated that Benin could sustain a net foreign liability position in the range of 40-60 percent of GDP, corresponding to current account deficits of 3-5 percent of GDP.